2019
DOI: 10.1371/journal.pone.0211804
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year change of knowledge and willingness by sampled respondents to perform bystander cardiopulmonary resuscitation in a metropolitan city

Abstract: BackgroundNationwide and regional interventions can help improve bystander cardiopulmonary resuscitation (CPR) awareness, knowledge, and the willingness. Periodic community investigation will help monitor the effect. This study aimed to compare the experience of CPR education, CPR knowledge, and CPR willingness, during a 5-year interval.MethodsThis is a pre and post study. Two surveys were done in February 2012 and December 2016. National and regional intervention including legislation promoting public involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
0
25
1
Order By: Relevance
“…After a 5-year intervention in Korea, the percentage of respondents who received CPR education increased from 36.2% to 55.1%, and scores on CPR performance increased from 1.6% to 11.7%. 33 In a matched-pair study among untrained Nigerian students, the question about the recommended rate of chest compressions was answered correctly by 10.5% of the participants preintervention and 43.8% postintervention. The mean knowledge score increased from 1.9 to 11.4.…”
Section: Discussionmentioning
confidence: 99%
“…After a 5-year intervention in Korea, the percentage of respondents who received CPR education increased from 36.2% to 55.1%, and scores on CPR performance increased from 1.6% to 11.7%. 33 In a matched-pair study among untrained Nigerian students, the question about the recommended rate of chest compressions was answered correctly by 10.5% of the participants preintervention and 43.8% postintervention. The mean knowledge score increased from 1.9 to 11.4.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted in Spanish high-school students reported lower percentages (58%) [30]. In other countries, similar percentages of participants of various lay population groups achieved sufficient training in CPR and AED use [25,27,31,32].…”
Section: Discussionmentioning
confidence: 98%
“…Helping lay rescuers recognize this fact might help better prepare them and avoid some of the negative psychological consequences [34,35]. Moreover, knowledge that friends and family might be e ciently helped by provision of BLS manoeuvres might increase lay rescuers motivation in acquiring and maintaining such critical skills [36].…”
Section: Discussionmentioning
confidence: 99%